The different influences of graphene quantum dots and N over oxygen reduction reaction. Issue 190 (13th June 2018) - He, Xiaohan; Zhao, Hong; Liu, Shuhong; Ding, Weiyuan; Liu, Dechong; Liu, Honghui; Xu, Hui
ABSTRACT: The scarcity and high cost of Pt-based electro-catalysts for oxygen reduction reaction (ORR) have limited their commercialization of fuel cells. N-doped carbon nano- materials have been demonstrated to be one of promising alternatives for ORR. In this paper, we investigated the different influences of Graphene Quantum Dots (GQDs) and N over ORR of N-doped GQDs (N-GQDs). TEM and various electrochemical measurements were carried out to characterize and test their catalytic activities for ORR in an alkaline medium. The results show that the quantity GQD and N have different influences on the ORR catalytic activities. Potential peak position shifts more positively as quantity of N increases, while current density mainly depends on the quantity of GQDs. C4 N79 (quantity of GQDs: 0.2 mg, quantity of N: 7.9 × 10 −3 mg) shows a four-electron reduction process similar to Pt/C for ORR and better methanol tolerance.